Genuine fraud - Lockhart, E. (New York : Delacorte Press, 2017)
Told through flashbacks, best friends Jule and Imogen are orphaned outcasts who will do almost anything to attain a happy, wealthy life.
Keywords: Best friends -- Fiction; Friendship -- Fiction; Deception -- Fiction; Impersonation -- Fiction; Orphans -- Fiction; Mystery and detective stories; Friendship -- Fiction; Deception -- Fiction; Impostors and imposture -- Fiction; Orphans -- Fiction; Mystery fiction